Referral for Imaging in Physical Therapist Practice: Key Recommendations for Successful Implementation. Issue 3 (29th January 2021) - Keil, Aaron Paul; Hazle, Charles; Maurer, Amma; Kittleson, Connie; Watson, Daniel; Young, Brian; Rezac, Scott; Epsley, Scott; Baranyi, Brian
Abstract: In recent years, the use of diagnostic imaging in physical therapist practice in the United States has gained considerable interest. In several countries around the world and in the US military, patient direct referral for diagnostic imaging has been considered normative practice for decades. US physical therapy program accreditation standards now stipulate that diagnostic imaging content must be included in physical therapist educational curricula. The American Physical Therapy Association has made efforts to pursue practice authority for imaging referral. A recent review of state practice acts and other statutory language concluded that many states have no prohibitions against physical therapists referring for imaging studies. Additionally, physical therapists can now pursue certification as musculoskeletal sonographers. In light of these advances, and with a growing number of physical therapists serving patients who have not yet seen another health care provider, it may be helpful for those who have been actively involved in the use of imaging in physical therapist practice to provide their collective recommendations to serve as a guideline to those interested in incorporating this practice privilege. The purpose of this perspective article is to provide an overview of the key elements necessary for effective implementation of referral for imaging in physical therapist practice while emphasizing the cornerstone of effective communication.